2002
DOI: 10.1128/aem.68.12.6043-6050.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Caedibacter Comprises Endosymbionts of Paramecium spp. Related to the Rickettsiales ( Alphaproteobacteria ) and to Francisella tularensis ( Gammaproteobacteria )

Abstract: Obligate bacterial endosymbionts of paramecia able to form refractile inclusion bodies (R bodies), thereby conferring a killer trait upon their ciliate hosts, have traditionally been grouped into the genus Caedibacter. Of the six species described to date, only the Paramecium caudatum symbiont Caedibacter caryophilus has been phylogenetically characterized by its 16S rRNA gene sequence, and it was found to be a member of the Alphaproteobacteria related to the Rickettsiales. In this study, the Caedibacter taeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 60 publications
1
60
0
Order By: Relevance
“…Interestingly, the branching of host and endosymbiont phylogenetic trees was congruent (22,114,117). This suggested that the ancestor of the C. caryophilus-related endosymbionts lived within an amoebal progenitor and coevolved with their hosts during the diversification of the different Acanthamoeba sublineages (22). If this is true, C. caryophilus will have only recently transferred to the ciliate Paramecium caudatum.…”
Section: Holosporaceaementioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, the branching of host and endosymbiont phylogenetic trees was congruent (22,114,117). This suggested that the ancestor of the C. caryophilus-related endosymbionts lived within an amoebal progenitor and coevolved with their hosts during the diversification of the different Acanthamoeba sublineages (22). If this is true, C. caryophilus will have only recently transferred to the ciliate Paramecium caudatum.…”
Section: Holosporaceaementioning
confidence: 95%
“…A recent phylogenetic analysis of the 16S rRNA genes of all these symbionts of Acanthamoeba, of the ciliate Paramecium caudatum (C. caryophilus, H. obtusa, and H. elegans) and of the shrimp Penaeus vannamei (NHP bacterium) showed that Candidatus O. thessalonicensis was phylogenetically close to Candidatus P. acanthamoebae (22). Interestingly, the branching of host and endosymbiont phylogenetic trees was congruent (22,114,117). This suggested that the ancestor of the C. caryophilus-related endosymbionts lived within an amoebal progenitor and coevolved with their hosts during the diversification of the different Acanthamoeba sublineages (22).…”
Section: Holosporaceaementioning
confidence: 99%
“…More recently, our knowledge of the diversity of bacteria associated with ciliates has increased significantly, primarily as a result of extensive molecular investigations of some commonly occurring species of the genera Paramecium and Euplotes. These studies have demonstrated that most bacterial symbionts belong to one of four classes of the phylum Proteobacteria, namely Alphaproteobacteria (including pathogenic Rickettsia) [2,8,9,18,19,21,22,51,59,60,62,64,67,69], Betaproteobacteria [58,63,66,68], Gammaproteobacteria [4,10,48,53] and Deltaproteobacteria [15]. Associations between ciliates and bacteria of other phyla seem to be infrequent, for example, Verrucomicrobia [42] and Firmicutes [54].…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic affiliation has been determined for only a few of these, i.e. Caedibacter caryophilus (Springer et al 1993), C. teniospiralis (Beier et al 2002), Holospora obtusa (Amann et al 1991), Polynucleobacter necessarius (Springer et al 1996), and 'Candidatus Devosia euplotis' (Vannini et al in press). Second, the significance of the symbiotic relationships and the possibility that the symbionts provide their host with selective advantages have been investigated.…”
Section: Introductionmentioning
confidence: 99%